2018
DOI: 10.24093/awej/call4.17
|View full text |Cite
|
Sign up to set email alerts
|

A Study of EFL Saudi Students' Use of Mobile Social Media Applications for Learning

Abstract: This research addresses the gaps in the literature on m-learning approaches in Saudi Arabia, with a focus on English as a Foreign Language (EFL) students studying at university level. The research aimed to explore university students' use of social media applications and their role in language learning, with a focus on how mobile devices can best be utilised. It analysed the attitudes of 102 learners towards the use of social media to improve language learning both inside and outside the classroom setting. Stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 3 publications
1
23
0
Order By: Relevance
“…The results of the current study revealed that the high usage level of smart devices among students for learning English is elated to students ' awareness and familiarity with the enormous capabilities and incredible opportunities that smart devices provide for language learning. This is in aligned with the results of previous studies [5], [12], [1], [2], [31], [30], [34], [16], [3], [4]. This study recommends that education policy makers design effortless and attractive language learning applications that are appropriate to students' needs.…”
Section: Discussionsupporting
confidence: 89%
“…The results of the current study revealed that the high usage level of smart devices among students for learning English is elated to students ' awareness and familiarity with the enormous capabilities and incredible opportunities that smart devices provide for language learning. This is in aligned with the results of previous studies [5], [12], [1], [2], [31], [30], [34], [16], [3], [4]. This study recommends that education policy makers design effortless and attractive language learning applications that are appropriate to students' needs.…”
Section: Discussionsupporting
confidence: 89%
“…Where participants included teachers (Aifan, 2015;Allam & Elyas, 2016;Alnujaidi, 2017 [Table 6]; Alshammari et al, 2017 [Table 3]; Alqasham, 2018b [ Table 5]), the researchers mainly focused on reactions to teaching interventions. Students were generally enthusiastic in their adoption of SNSs, as evident in Table 6 (Aifan, 2015;Kutbi, 2015;Alnujaidi, 2017;Alshabeb & Almaqrn, 2018;Sharma, 2019). Twitter and WhatsApp were especially popular applications (Alsharidi, 2018 [Table 2]; Alshammari et al, 2017;Alkhatnai, 2019 [Table 3]; Alqasham, 2018a& 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…Another concern is the lack of any formal guidelines or policy on using SNS in the classroom. Teachers also complained that its 24/7 availability could be a nuisance and that too much familiarity impaired teacher-student relations (Alnujaidi, 2017;Alshabeb & Almaqrn, 2018;Sharma, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the results showed that learners study better through using their mobiles and mobile phone applications. Alshabeb and Almaqrn (2018) explored the use of social media applications in language learning among university students. They focused on the use of mobile devices in students' learning.…”
Section: Literature Reviewmentioning
confidence: 99%